The Idiom of the Classical Guitar: Analysing the Concept in Relation to the Challenges of Contemporary Repertoire - Marcin KUŹNIAR (Edukacja Muzyczna)
The term ‘idiom of the classical guitar’ is frequently used to intuitively identify the set of characteristics associated with this instrument. It serves as a cognitive shortcut, referencing the particulars of the instrument in general. In this context, intuition frequently leads to the exploration of Iberian roots and Latin American popular music. However, each period has seen new advances in performance technique and perception of the instrument, which have broadened the definition of the idiom. Contemporary compositions demand a continual reassessment of what is perceived as ‘natural’ and therefore suitable for performance on the guitar. This article presents a historical account of the formation of the term guitar idiom, offers a critical analysis of the various interpretations of its meaning, identifies the essential criteria for defining a composition as idiomatic, develops a comprehensive definition of idiomaticity, and addresses the question of whether, in view of the incompatibility of interpretations and the ongoing expansion of the semantic framework of the guitar idiom, its use should be abandoned. In order to achieve this objective, the article presents the perspectives of modern scholars and artists in juxtaposition with an analysis of recent musical compositions that represent significant milestones in the evolution of the guitar’s idiomatic potential.